Frequency-dependent conversion of the torque of a rotating magnetic field on a ferrofluid confined in a spherical cavity. Issue 44 (1st November 2019) - Usadel, Klaus D.; Storozhenko, Anastasiya; Arefyev, Igor; Nádasi, Hajnalka; Trittel, Torsten; Stannarius, Ralf; Veit, Peter; Eremin, Alexey
Abstract : The dynamics of magnetic nanoparticles in rotating magnetic fields is studied both experimentally and theoretically. Abstract : The dynamics of magnetic nanoparticles in rotating magnetic fields is studied both experimentally and theoretically. The experimental investigation is focused on the conversion of the magnetic forces to a mechanical torque acting on a ferrofluid confined in a spherical cavity in a rotating magnetic field. Polydispersity usually present in diluted ferrofluids is shown to play a crucial role in the torque conversion. Important features observed experimentally are reproduced theoretically in studies on the dynamics of particles with uniaxial magnetic anisotropy in the presence of thermal noise. The phase lag between the rotating magnetic field and the induced rotating magnetization, as well as the corresponding torque which is transferred to the carrier fluid because of the mutual coupling between both, is analyzed as a function of the particle size. It is shown that for large particles the magnetic moment is locked to the anisotropy axis. On lowering the particle radius, Néel relaxation becomes increasingly important. Illustrative numerical calculations demonstrating this behavior are performed for magnetic parameters typical for iron oxide.